2022
DOI: 10.1021/acs.jmedchem.2c01518
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Receptor-Interacting Protein 1 (RIP1) Inhibitors as Therapeutic Agents for Multifaceted Diseases: Current Medicinal Chemistry Insights and Emerging Opportunities

Abstract: As a serine/threonine protein kinase, receptor-interacting protein 1 (RIP1) plays an important role in regulating the pathways in programmed cell death. Multifaceted human diseases (e.g., autoimmune diseases, inflammatory diseases, neurodegenerative diseases, and tumors) are closely related to RIP1 kinase. Therefore, small-molecule RIP1 inhibitors with precise targeting and good penetrability have recently been used in potentially therapeutic methods, attracting extensive researcher interest. GSK2982772, devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 149 publications
0
11
0
Order By: Relevance
“…Compound 30 with Frontiers in Chemistry frontiersin.org fluorine is the most potent compound of the entire series (IC 50 = 0.01 nM), with 40-fold higher potency than GSK'157. To the best of our knowledge, this is the most potent necroptosis inhibitor ever reported (Martens et al, 2020;Chen et al, 2022;Shi et al, 2022). However, compared to the corresponding pyridinyl analogues (18-20), the phenyl analogues 30-32 retained some PERK inhibition, albeit at concentration higher than 1 µM which still results in excellent selectivity.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Compound 30 with Frontiers in Chemistry frontiersin.org fluorine is the most potent compound of the entire series (IC 50 = 0.01 nM), with 40-fold higher potency than GSK'157. To the best of our knowledge, this is the most potent necroptosis inhibitor ever reported (Martens et al, 2020;Chen et al, 2022;Shi et al, 2022). However, compared to the corresponding pyridinyl analogues (18-20), the phenyl analogues 30-32 retained some PERK inhibition, albeit at concentration higher than 1 µM which still results in excellent selectivity.…”
Section: Discussionmentioning
confidence: 90%
“…Particularly, the co-crystallization of Nec-1s, a stable form of Nec-1, with the kinase domain of RIPK1 demonstrated the typical type III kinases inhibitor mode of interaction, with binding to the specific RIPK1 allosteric pocket formed by the DLG-out conformation and without interacting with the hinge region (Wang et al, 2006;Zheng et al, 2008;Takahashi et al, 2012). Since then, several additional RIPK1 inhibitors have been reported (Martens et al, 2020;Chen et al, 2022;Shi et al, 2022). Among them, a class of compounds featuring a benzoxazepinone core emerged with GSK2882481 (Clark et al, 2009;Harris et al, 2016), but interspecies differences were observed when comparing humans to non-primate RIPK1, probably due to the different amino acids featured by the enzyme affecting protein flexibility (Berger et al, 2015;Harris et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reader is directed to another review for further details on these recently identified scaffolds. 142 4.2. Inhibitors of RIPK3.…”
Section: Development Of Necroptosis Inhibitorsmentioning
confidence: 99%
“…Various other inhibitors of RIPK1 have been identified (structures not shown); however, as many of these compounds were developed as inhibitors of other kinases or are hits from library screens without optimization, these scaffolds primarily serve as a demonstration of the increasing efforts being directed toward the discovery and development of RIPK1 inhibitors as therapeutics. The reader is directed to another review for further details on these recently identified scaffolds …”
Section: Development Of Necroptosis Inhibitorsmentioning
confidence: 99%